Fecal specimens preparation methods for PCR diagnosis of human taeniosis - Nunes, Cáris Maroni [UNESP]; Lima, Luiz Gustavo Ferraz [UNESP]; Manoel, Camila Santos [UNESP]; Pereira, Rodrigo Norberto [UNESP]; Nakano, Mauro Massaharu [UNESP]; Garcia, José Fernando [UNESP] (Wiley, 2006)
Sample preparation and DNA extraction protocols for DNA amplification by PCR, which can be applied in human fecal samples for taeniasis diagnosis, are described. DNA extracted from fecal specimens with phenol/chloroform/isoamilic alcohol and DNAzol® reagent had to be first purified to generate fragments of 170 pb and 600 pb by HDP2-PCR. This purification step was not necessary with the use of QIAmp DNA stool mini kit®. Best DNA extraction results were achieved after eggs disruption with glass beads, either with phenol/chloroform/isoamilic alcohol, DNAzol® reagent or QIAmp DNA stool mini kit®.
Keywords: DNA extraction; Fecal specimens; Polymerase chain reaction (PCR); Taenia saginata